2001
DOI: 10.1542/peds.108.5.e91
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Dimensions of the Healthy Preterm Infant

Abstract: ABSTRACT. Background. The diaphragm is the major inspiratory muscle in the neonate; however, human neonatal diaphragm development has not been extensively studied. We hypothesized that diaphragm thickness (t di ) would be positively related to postmenstrual age (PMA), body weight, body length, head circumference, and nutritional intake.Objectives. To evaluate the evolution of diaphragm growth and motion in the healthy, preterm infant.Methods. We used ultrasound to measure t di at the zone of apposition to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
2
22
1
Order By: Relevance
“…The latter finding may be due to the small range of gestational ages among our subjects (GA between 37 and 40 wk). The absence of any correlation between t di and GA in term infants is in contrast to our finding of a significant correlation between t di and GA (between 26 and 37 wk) in premature infants (20).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The latter finding may be due to the small range of gestational ages among our subjects (GA between 37 and 40 wk). The absence of any correlation between t di and GA in term infants is in contrast to our finding of a significant correlation between t di and GA (between 26 and 37 wk) in premature infants (20).…”
Section: Discussioncontrasting
confidence: 99%
“…In support of this notion, we found that t di scaled with BW to the power of 0.57, i.e. t di $ BW 0.57 , which is similar to the relationship between t di and BW that we previously determined in preterm infants (t di $ BW 0.61 ) (postmenstrual age, 26-37 wk) (20).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that the ROC for tdi end-expiration was less than that for Δtdi% alone (0.79 for Δtdi% and 0.61 for tdi end-expiration). The failure of this model to improve extubation predictions may be related to the variability of tdi among individuals24 25 or the presence of ventilator induced diaphragm atrophy in some but not other patients 3. We reasoned that the product of Δtdi% and V T may be a better predictor of extubation success than Δtdi% alone.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming the same relative organ proportions as in the adult, a normal neonate weighing 3000 g would have a diaphragm that weighs approximately 12 g and is approximately 2 mm thick (26). Indeed, roughly similar dimensions are observed in preterm infants weighing between 1260 g and 2100 g who have diaphragms that are between 1.09 (±0.08) and 1.74 (±0.04) mm thick (27). An increase in diaphragm size correlates directly with inspiratory force (28), and full-term infants reach adult levels of Pdi max at approximately 6 months of age (25).…”
Section: Diaphragm and Survivalmentioning
confidence: 69%